Vibe : unlock the energetic frequencies of limitless health, love & success - Openshaw, Robyn (North Star Way, 2017)
"In [This book] ... author Robyn Openshaw reveals the difference between low vibration emotions (fear, anger, inertia) and high vibration emotions (love, inner peace, and gratitude) helps readers dramatically impact their physical and mental well-being by raising their vibrational frequencies. The great Austrian scientist Nikola Tesla is a household name among today's scientific community, known for his finding that all matter has vibrational energy, or electrical frequency, and that we are all electrical beings, made up of rapidly vibrating cells. Most of us are vaguely familiar with this concept, but we don't realize the powerful implications this has for our choices every day-- which foods to eat, how much water to drink, what we think about when we're in the car or the shower, what our risk of disease is, and how we feel at any given moment are all affected by the power of vibration. Everything in health and wellness should revolve around the basic concept that what we choose to eat and what we choose to do lowers or raises our vibration. And that makes all the difference. Vibe explores the foods, natural substances, and lifestyle practices that can raise our vibrations. Robyn Openshaw reveals evidence that shows how drinking green juice, using certain essential oils, and engaging in yoga and meditation raises the frequency of the human brain and other organs. Living in a "high vibe" state can make us resilient to illness, fatigue, burnout, and depression. Readers will learn all about the low vibration emotions (fear, anger, inertia) and the high vibration emotions (love, peace, gratitude) and how to achieve higher vibrations in everyday living. Openshaw explores how the smallest changes in our life-- from what we eat to how we think-- can radically improve our mood, overall health, and quality of life"--